2018
DOI: 10.1080/10646175.2018.1491433
|View full text |Cite
|
Sign up to set email alerts
|

White Norm, Black Deviation: Class, Race, and Resistance in America’s “Postracial” Media Discourse

Abstract: The authors deploy Marxist theory-and Gramscian hegemonic theory in particular-to investigate the subtleties of racial "othering" in the media representations of African Americans in a putatively postracial America. The paper's objects of inquiry are an opinion article in the Atlanta Journal-Constitution and the reaction it instigated in the Atlanta Black Star. We argue that the contestations of signification between the dominant narrative about African Americans in the Atlanta Journal-Constitution and the rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…[...] He grows flowers there [laughing, possibly meaning marijuana]." The roles the participants assigned to, and the media narratives they created with, the Black African/Caribbean adult male with dreadlocks had some similarities with research that suggests that, in the US media discourse, African Americans are often portrayed as criminals who find themselves in difficult situations as a result of their own choices (Fabregat & Kperogi, 2019;Hart, 2013;Willet & Willet, 2013).…”
Section: Table 2 the Companions And The Enemiesmentioning
confidence: 99%
“…[...] He grows flowers there [laughing, possibly meaning marijuana]." The roles the participants assigned to, and the media narratives they created with, the Black African/Caribbean adult male with dreadlocks had some similarities with research that suggests that, in the US media discourse, African Americans are often portrayed as criminals who find themselves in difficult situations as a result of their own choices (Fabregat & Kperogi, 2019;Hart, 2013;Willet & Willet, 2013).…”
Section: Table 2 the Companions And The Enemiesmentioning
confidence: 99%
“…On this basis, Dekker and van der Noll (2009) observed that Muslims generally have high poverty levels, below average education, live in poorer areas of towns and cities, are overrepresented in low-wage jobs and have little access to standard healthcare. They share these situations with other minority communities such as blacks, Irish, Hindus, Boers and Latinos (Fabregat & Kperogi, 2018;Halliday, 1993). However, what makes Muslims stand out according to Perroco (2018), is that theirs "is the deepest, most acute and widely spread form of racism" (p. 26); in the words of Nazroo and Bécare (2017, p. 31), they "are repeatedly described as the social group most frequently discriminated against."…”
Section: Scholars Like Fredmentioning
confidence: 99%